The Importance of Supervision Implementation in Educational Institution - Hasnadi Hasnadi (Jurnal Dedikasi Pendidikan, 2021)
Educational supervision is an activity carried out by supervisors through the process of mentoring, coaching, providing information and knowledge to the teachers and headmaster as an effort to improve and to increase the competency, performance, quality of learning, professional development, and achievement of educational objectives. This study aims to describe the urgency of supervision implementation in educational institutions. This study used literature review approach: it is the description of theory and result of research that has been conducted as the research foundation. Supervision would be conducted democratically, comprehensively, constructively, objectively, and continuously through collegial, clinical, individual and artistically approach which are appropriate with the condition of the educational institutions. Supervision is important to do because through the supervision, it would motivate and improve the performance of headmaster, teachers, and other staffs, improve and develop the quality of education, and also achieve the educational objectives. The supervisors in carrying out the duties and functions should role as the consultant, coordinator and lead evaluator by creating harmonious relationship, honest, cooperative, patient, and a role model with other good attitudes.